PERANCANGAN MEDIA PROMOSI HOTEL SAHADEWA RESORT & SPA UBUD BALI - Putra, I Putu Raditya Kusuma; Putra, Gede Bayu Segara; Kharismawan, Putu Gde Satria (Program Studi Desain Komunikasi Visual, 2025)
The design of promotional media for Sahadewa Resort and Spa aims to increase brand awareness in the midst of intense competition in the hospitality industry in Ubud. As a favorite tourist destination, Ubud has attractions in the form of natural beauty, cultural arts, and customs that attract domestic and foreign tourists. However, the mismatch between the hotel's great potential and the low utilization of effective promotional media to reach a wider audience can reduce its attractiveness and exposure in the highly competitive hospitality market. Therefore, a promotional media in the form of a flyer with a minimalist visual design was designed. This flyer design has a natural serenity concept that carries a minimalist, simple, clean and elegant style with attractive visual elements. The use of bright colors, typography and strategic placement of elements to maximize promotional messages. The flyer design process involves design principles such as balance, unity, contrast, rhythm, and proportion that help to create an aesthetic and communicative design. The data collection methods used are interview, observation, literature study and documentation. The results of this promotional media design are expected to strengthen the position of Sahadewa Resort and Spa in the Ubud hospitality market. Increase attractiveness in the eyes of tourists, and expand the reach of promotion through effective media. Accordingly, this hotel promotional media design discusses the importance of visual communication design in promoting tourist destinations and how design elements can contribute to the effectiveness of the message given to the audience.